AFF2 Is Associated With X-Linked Partial (Focal) Epilepsy With Antecedent Febrile Seizures - Zou, Dongfang; Qin, Bing; Wang, Jie; Shi, Yiwu; Zhou, Peng; Yi, Yonghong; Liao, Jianxiang; Lu, Xinguo (Frontiers in Molecular Neuroscience, 2022)
Objective AFF2 mutations were associated with X-linked intellectual developmental disorder-109 and in males with autism spectrum disorder (ASD). The relationship between AFF2 and epilepsy has not been defined. Method Trios-based whole-exome sequencing was performed in a cohort of 372 unrelated cases (families) with partial (focal) epilepsy without acquired causes. Results Five hemizygous missense AFF2 mutations were identified in five males with partial epilepsy and antecedent febrile seizures without intellectual disability or other developmental abnormalities. The mutations did not present in the controls of general populations with an aggregate frequency significantly higher than that in the control populations. Previously, intellectual disability-associated AFF2 mutations were genomic rearrangements and CCG repeat expansion mutations mostly, whereas the mutations associated with partial epilepsy were all missense. Missense AFF2 mutations associated with epilepsy fell into the regions from N-terminal to the nuclear localization signal 1 (NLS1), while ASD-associated missense mutations fell in the regions from NLS1 to C-terminal. Conclusion AFF2 is potentially a candidate causative gene of X-link partial epilepsy with antecedent febrile seizures. The genotype–phenotype correlation and molecular sub-regional effect of AFF2 help in explaining the mechanisms underlying phenotypic variations.